Analysis of the Quality of Tryout Questions in the Marketing Education Program Based on Pedagogical Content Knowledge for UKPPPG Readiness - Hidayat, Rachmad; Rahayu, Wening Patmi (Transpublika Publisher, 2025)
A fundamental issue in the educational ecosystem is the assessment of learning outcomes. In preparing teachers for the Teacher Professional Education Competency Test (UKPPPG), tryout tests serve as strategic instruments. For the Marketing Education Program, these test items must reflect required pedagogical and professional competencies, particularly Pedagogical Content Knowledge (PCK), which integrates content mastery with teaching strategies. This study aims to analyze the quality of tryout test items based on PCK in preparing Marketing Education Program teachers for the UKPPPG. Using a quantitative-descriptive approach with 108 participants (36 male; 72 female), data were analyzed with SPSS 31, focusing on item validity (point-biserial correlation), reliability (Cronbach's α), discrimination index (D), difficulty level (p), and distractor effectiveness. Results indicate sufficient reliability (α = 0.760), though item quality varied: some items were valid, marginal, or invalid—particularly weak in early indicators. Discrimination indices were mostly